ANALISIS KINERJA EKSPOR KERTAS INDONESIA KE AMERIKA LATIN - Mira Marina; Sri Mulatsih (IPB University, 2016)
In order to increase the trade flow, Indonesia joined an alliance called as SouthSouth Cooperation and Forum for East Asia-Latin America Cooperation (FEALAC). One of commodity exported by Indonesia to Latin America is paper. This research purposes to analyze the competitiveness of Indonesian paper commodity in Latin America, and finding out factors affect paper export Indonesia to Latin America during 2009-2013, using RCA, EPD, gravity model and Porter’s Diamond method. This research revealed that the average of RCA is more than 1; three countries placed on the rising star, one country on lost opportunity position, two countries on falling star position, and two countries in retreat position. Variables affect export volume significantly are Per capita riel GDP of Indonesia and export destination country, export price, and economic distance, while exchange rate is not significantly affect the the exports. Keywords: Competitiveness, EPD, Gravity, Porter’s Diamond, RCA